Suitability Analysis of Fish Apartment Placement to Conserve Fish Resources on the North Sea of East Java - Muliawati Handayani; Sukandar; Citra Satrya Utama Dewi; Dwi Puji Hartono (Jurnal Biologi Tropis, 2023)
Northern Java have been overexploited due to over fishing and use of destructive fishing gear. This causes a decrease in fish resources. Fish apartment is alternative things to restore the availability of fish resources. Drowning a fish apartment requires a more effective suitability assessment and to maximize its benefits. This study aims to know the suitability/feasibility of candidate locations for placing fish apartment. The study was conducted in April-June 2019 used survey and assess the condition of the waters based on the suitability matrix. The assessment score multiplied by the point of each parameter. The result showed that, placement of fish houses in Tuban district is in Palang waters; Bangkalan Regency in Modung Waters, Pamekasan Regency in Jumiang 3 site, Gresik Disctict (Bawean Island) in Batu Elong, Probolinggo Regency in Gending Waters, Probolinggo City in Karang Katon Waters and Situbondo Regency in Pasir Putih Beach.